(untitled) (Kairaranga, 2008)
Participatory action research advocates for teachers, parents and others to engage in practical inquiry as part of their everyday work for the purpose of improvement. Findings from this project affirm that a collaborative community of researchers, one in which the participants can critically analyse and transform their own situations, can have a significant impact on outcomes for students with autism spectrum disorder (ASD) (Meyer, Park, Grenot-Scheyer, Schwartz & Harry, 1998). This article identifies the shifts in perspectives resulting from engagement with this process for a team of adults. It also identifies the features of the team’s experience that offer effective ways to work with students with AD and their families.